IMPLEMENTASI MODEL PEMBELAJARAN CHILDREN LEARNING IN SCIENCE (CLIS) BERBASIS LESSON STUDY UNTUK MENINGKATKAN AKTIVITAS BELAJAR PESERTA DIDIK - Meilanisa, Irdya; Harjati, Purwiro; Alarifin, Dedy Hidayatullah (Universitas Muhammadiyah Metro, 2022)
Abstract: The result of prasurvey that has been done on the UPTD SMP Negeri 7 Metro obtained a good learning conditions. However, students learning activities are still classified as low. Therefore, there needs to be an improvement in the learning process by using the Children Learning In Science learning model based on Lesson Study to enhance the learning activities of students. Several stages of CLIS learning model include orientation, rendering the notion, the idea of reorganization, implementation of the idea, and the establishment of the idea. This research is a classroom action research (CAR) which cycle with the stage plan (planning), do (execution) and see (reflection). The subjects of this study were students of UPTD SMP Negeri 7 Metro class VIII.E which amounted to 27 students. Data collection instruments used were observation sheet of students learning activities and field note. The results showed that the implementation of the Chikdren Learning In Science (CLIS) model based on Lesson Study was able to improve the learning activities of students with indicators of achievement of learning activities including paying attention to the explanation or affirmation of the material by the teacher, preparing tools, arranging tools, doing group assignments, discussing with group, answer, respond or ask questions and work on questions. The percentage of increased learning activities in cycle 1 was 60.98% in cycle 2 of 83.49%. The category of increasing learning activities of students is very highKeywords: Children Learning In Science model, Lesson Study, learning activities.